Between work boots and heels: dress code in Maria Elena’s office - Guarello, José (Revista Chilena de Antropología, 2023)
This article investigates the clothing in the María Elena saltpetre office during the Guggenheim extraction cycle, focusing on the footwear used by the residents. Socio-cultural differences based on class and gender are analysed, and the context, use, and meaning of the male "calamorro" shoes and the women’s high-heeled shoes are examined. The research is based on interviews conducted by the research team, on-site photographic material, and excerpts from local literature addressing life in the saltpetre pampa. Through these elements, the article aims to preliminarily explore how shoes can provide information about the way of life of workers and women in a 20th-century mining company that operated as a planned community.